Metody estymacji rozkładów opóźnień czasowych - Skąpski, Tomasz (Wydział Prawa i Administracji UAM, 1975)
The author deals with the principle estimation methods of the lag distribution. The lag estimation with help of the interpolation polynomial and with help of the Pascal distribution has been broad discussed.
Estimation Methods of the Lag Distribution